Analisis resiliensi rumah tangga petani ubi Cilembu dalam menghadapi serangan organisme pengganggu tanaman - Siti Nuriyah Hasanah; Endah Mulyani; Novita Dyah Wulandari; Alya Fauzia; Nia Kurniawati Hidayat (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
Cilembu sweet potato is a typical variety of Cilembu Village, Sumedang Regency. The pattern of continuous cultivation of Cilembu sweet potato can threaten the existence of local resources (ecological niche) so that Cilembu sweet potato is no longer a superior commodity typical of Sumedang Regency. The objectives of this research are (1) to identify the conditions of commercialization of Cilembu sweet potato; and (2) analyzing the condition of vulnerability and resilience efforts of Cilembu sweet potato farmers. The research was conducted in Cilembu Village as the origin of the Cilembu sweet potato variety. Determination of the sample was carried out through simple random sampling technique and obtained as many as 74 Cilembu sweet potato farmers who were still actively planting Cilembu sweet potato. Primary data was obtained through a direct survei for approximately two weeks in early July 2022. The results of the research are (1) as many as 68 farmers (92%) of Cilembu sweet potato farmers are commercial farmers and the other eight percent are preservation farmers; and (2) preservation farmers are able to prevent the impact of pest attacks compared to commercial farmers.